Genetic Characterization of South African and Australian Purebred Boer Goats and Australian Crosses Using Microsatellites - Ali Kamarulzaman, Hamidah (2010)
The Boer goats which originate from South Africa are raised as meat goats across the American, Australia and Asia continent. They are being continuously imported into Malaysia from South Africa and Australia. However, lack of information is available on the breed’s genetic characteristics or genetic variability. Comprehensive knowledge of the existing genetic variability of a species is a core element for conservation and exploitation of animal diversity for breeding purposes. When exotic breeds are imported into a country, unless proper breeding programs are implemented and adhered to, the unique characteristics of the breed might become diluted due to crossbreeding with other breeds, sub-structuring or genetic drift. This study was conducted to evaluate the genetic variability within and between the purebred of South African and Australian Boer goats and the Australian Boer crosses in Malaysia using microsatellite markers. Blood samples were randomly sampled from 50 purebred Boer goats from South Africa (SA), and 50 purebred Boer goats (AUS) and 30 crossbred Boer goats (CRS) from Australia. Thirty microsatellite loci suggested by FAO for genetic diversity studies in goats plus 20 microsatellite loci reported as polymorphic in other studies on goats were used. Optimization of polymerase chain reaction (PCR) protocols and preliminary screening to detect polymorphic loci were carried out using DNA pools. The status of the monomorphic loci was confirmed by screening seven individual samples from each population. The loci detected as polymorphic were then used in the analysis of individual sample. Only 46 of the microsatellite loci were successfully amplified, of which 15 were monomorphic and 31 were polymorphic. Eighteen polymorphic loci were from the panel recommended by FAO. The mean number of observed alleles was 2.39 for all the populations and the allele sizes ranged from 31 to 330 bp. The observed heterozygosity values (Ho) were higher than the expected heterozygosities. The CRS population had the highest Ho (0.52), followed by AUS (0.51) and SA (0.45) populations. The polymorphic information content values for the loci investigated ranged from 0.11 (INRABERN185) in the SA population to 0.64 (TGLA53) in the AUS population. No linkage disequilibrium was found among the loci used in the study. Significant heterozygosity excess on the basis of the Infinite Allele Model, Two Phase Model and Stepwise Mutation Model revealed by the Wilcoxon sign-rank test, along with the absence of L-shape distribution in the mode-shift test for allele frequency classes, indicated no inbreeding in the SA, AUS and CRS populations. The overall mean inbreeding coefficient (FIS) of 0.02 also supported this. Wright’s fixation index (FST) was -0.09 indicating the absence of genetic differentiation among the three Boer breed types. The Nei’s genetic similaritiy between SA and AUS was 99%, and between CRS and SA and between CRS and AUS were 98%. Analysis of molecular variance (AMOVA) indicated that of the total genetic variation 99% was attributed to within population variation and only 1% was due to among population variation. The present study shows that the AUS and CRS populations have moderate genetic diversity, while SA has a slightly lower genetic diversity. The purebred Boer goats from South Africa and Australia are very similar in their genetic makeup. The three Boer breed types are not genetically distinct. However, further screening of the Boer goat types with more populations of each type and more microsatellite loci are needed before drawing any definite conclusions. Capillary electrophoresis of the microsatellite alleles and other more sensitive genetic marker systems, such as single nucleotide polymorphism (SNP), should also be considered. The information derived from the present study about the Boer goat populations from South Africa and Australia and the crossbred Boer goats using microsatellite analysis serves as preliminary results for planning breeding designs and for future studies.